Peran Pos Lintas Batas Negara Motamasin dalam Mengatasi Imigran Ilegal di Wilayah Perbatasan RI-RDTL - Maria Vianey Gunu Gokok; Tanti Nurgiyanti; Diansari Solihah Amini; Yeyen Subandi (Yayasan Literasi Sains Indonesia, 2023)
Transnational crime is defined as a criminal act or crime that crosses the borders of a country and can threaten the sovereignty of that country. Based on the United Nations Convention on Transnational Organized Crime (UN TOC), illegal immigrants are included in one of the transnational crimes. This study aims to examine the role of the Motamasin PLBN in overcoming the problem of Illegal Immigrants in the border region of the Republic of Indonesia and the Democratic Republic of Timor Leste. In the description, this study uses a qualitative method, and the concept of transnational crime and the concept of the role of the state. PLBN as a border gate was built as an effort to maintain order in border areas so that as a representation of the state in areas bordering other countries, PLBN takes an important role in upholding state sovereignty and improving the welfare of people in border areas. In dealing with Illegal Immigrants, PLBN Motamasin acts as a coordinator and facilitator between immigration and neighboring country cross-border posts to carry out various Immigration Administrative Actions against foreigners who violate the Indonesian Immigration Law.